Chlorophyll content of Thalassia hemprichii (Ehrenberg) Ascherson leaves in some coastal areas of Cebu Island, Central Philippines - Halasan, Lorenzo C.; Dy, Danilo T. (Annals of Tropical Research, 2018)
Variations in the chlorophyll concentrations in seagrass leaves can be used to indicate biomass, productivity and overall ecosystem condition in coastal areas. In this study, we determined the chlorophyll content (ie chl a and b) of Thalassia hemprichii from selected coastal areas in Cebu Island, Central Philippines to determine if there were spatial variations between intertidal (0m) and subtidal (1.5m) sections, and in the five geographically separate coastal areas of the island. Pigment extraction was done using 95% acetone, the solution analyzed via spectrophotometry and quantified using the equation of Ritchie (2006). The values were statistically compared using nonparametric tests. Mean chlorophyll content and chlorophyll a/b ratio of T. hemprichii showed no significant variations between intertidal and subtidal sections: F(4,45)=27.75, p=0.192 for mean chlorophyll content and F(4,45)=18.28, p=0.116 for chlorophyll a/b ratio. However, there was significant difference between geographic areas (p=0.000). Although T. hemprichii tend to display a physiological response to shading and light limitation, the difference in depth (≈ 1.5m) between intertidal and subtidal sections did not produce a statistically meaningful difference. However, the significant differences between sites for the chlorophyll content and chlorophyll a/b ratio of T. hemprichii could guide future decision in seagrass transplantation of specific localities.